2017
DOI: 10.1080/08869634.2017.1342890
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin-1 and temporomandibular disorder: Contemporary review of the literature

Abstract: Articles that compared IL-1 concentrations in TMD vs. control groups found significant differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Notably, the complex balance between the molecules and receptors of the IL-1 family significantly impacts the TMJ homeostasis, as indicated in many research, which illustrated the presence of higher degrees of IL-1α and IL-1β in the synovial fluid of patients with TMDs [27]. In this study, the synovial fluid samples were extracted from patients with TMDs at diverse phases, which led to the conclusion that the increased degrees of these cytokines result in the development and progress of TMD [89].…”
Section: Il-1mentioning
confidence: 79%
“…Notably, the complex balance between the molecules and receptors of the IL-1 family significantly impacts the TMJ homeostasis, as indicated in many research, which illustrated the presence of higher degrees of IL-1α and IL-1β in the synovial fluid of patients with TMDs [27]. In this study, the synovial fluid samples were extracted from patients with TMDs at diverse phases, which led to the conclusion that the increased degrees of these cytokines result in the development and progress of TMD [89].…”
Section: Il-1mentioning
confidence: 79%
“…The intricate balance of molecules and receptors of the IL-1 family has a deep effect on the TMJ homeostasis. Many studies indicated that higher levels of IL-1α and IL-1β are present in the synovial fluid of patients with TMD 46 .…”
Section: Interleukin-1 (Il-1)mentioning
confidence: 99%
“…As an important inflammatory cytokine in the initiation and development of TMD, IL-1 β was widely used to simulate the inflammatory microenvironment of TMD in vitro[ 10 , 11 ]. In this study, we showed that IL-1 β inhibited the autophagy and chondrogenic differentiation of SMSCs.…”
Section: Introductionmentioning
confidence: 99%